Pemanfaatan Sludge dengan Campuran Black Liqour dan Tempurung Kelapa sebagai Bahan Pembuatan Biobriket - Njoman Manik Susantini; Rohmi Oktariani (Institut Teknologi Sains Bandung, 2021)
Process industries such as the pulp and paper industri produce solid waste (sludge) which can actually be utilized, one of which is by turning it into biobriquettes. In this research, biobriquette will be made from sludge with a mixture of black liquor and coconut shell. In this research, the raw material ratio is used as the independent variable, while the fixed variable is the drying time of the biobriquette. This research used the value of calorific, moisture content and ash content as dependent variables. This biobriquette making uses 6 variations of composition with sludge as the dominant material. The calorific value, ash content and moisture content of this biobriquette will be compared with coal. The calorific value of biobriquette with a variation of 60% sludge- 5% black liquor- 35% coconut shell (variation F) had the highest calorific value, namely 4543 cal / g. This value of 4543 cal / g is higher than the standard according to Permen ESDM No.47 / 2006, where the standard in Permen ESDM No.47 / 2006 is 4400 cal / g. For moisture content, this F variation has the lowest water content, namely 54.59%. In the F variation also, the resulting biobriquette ash content was the lowest, namely 5.74%.